Strategi Berkelanjutan Pemberdayaan Masyarakat Desa Melalui Komunitas Lokal: Studi Kasus Kabupaten Magelang - Abdurrahman Alauddin; Azizah Fathma; Lina Af’ida Fataya Helwa (Jurnal Community, 2023)
This article aims to explore the concept of local community in Magelang by using the concept of non formal education called as UNIDES (Universitas Pemuda Desa Indonesia). UNIDES is one of the local communities that aims to build human resources in the village so that they have a more advanced mindset. Trying to figure it out the key strategies, so that UNIDES as a local community can continue the program. By using qualitative method with case study approach, the data collection techniques sourced from field survey, depth interview, and focus group discussion. The result of this study shows that there are four startegies regarding to develop the sustain of local community organization (UNIDES) such as (1) Establish a business incubation program for increasing economic self-reliance, (2) Build a financing unit to gain capital business, (3) strengthening relations between community, students, and local government to implementing long term program of local community, and (4) Improve the capacity and capability of management UNIDES,  in order to create an empowered and prosperous society.